Cyberweapons: power and the governance of the invisible. Issue 3 (May 2018) - Stevens, Tim
Abstract This article explores the non-emergence of a global governance regime for cyberweapons. Cyberweapons are malicious software entities deployed to cause harm to adversaries' computer networks and systems. They threaten the integrity and functionality of digital systems that enable global circuits of communication and exchange, with significant potential impacts on social, economic and political order. Using a power-analytical approach, this article identifies four areas in which power works to constrain regime formation: the productive power of NATO's Tallinn Manual Process; the structural power of US involvement in cyberweapons markets; the institutional power of Internet technologies; and diplomatic claims to sovereignty that mask operations of compulsory power. These work together to prevent a unified global approach to the regulation of cyberweapons. The article concludes that there are substantial obstacles to effective cyberweapons governance but that these should not prevent ongoing efforts to tackle this important and ubiquitous security issue.